3 Answers | Add Yours
The equation to be solved is : (x+2)(x-1)-(2x+5)=-7
open the brackets
=> x^2 - x + 2x - 2 - 2x - 5 = -7
=> x^2 - x -7 = -7
=> x^2 - x = 0
=> x(x - 1) = 0
=> x = 0 and x = 1
The solution of the equation is x = 1 and x = 0
I think this did help. I have solved it a few times but I am gonna give it a break and see if I can still do it.
Well, first you simplify the equation:
Then by using the Addition Property of Equality (APE),
Since it's a quadratic equation, it becomes
x=0, or x=1.
I hope I've helped. :)
We’ve answered 317,514 questions. We can answer yours, too.Ask a question